Old Order Amish Family Management of Children With Genetic Conditions. (November 2021) - Kueny, Angela M.; Ayres, Lioness; Tripp-Reimer, Toni
Families who raise children with genetic conditions manage health care within the context of cultural communities. For Amish families, although genetic conditions are prevalent and have been well reported, few studies document family management of these conditions. This article describes Amish family management strategies in light of the Family Management Framework's contextual factors. Ethnographic data captured variations in perspectives from Amish families with children with diverse genetic conditions, Amish community members, and health care providers. Findings describe families at the center of decision making and health care management for children with genetic conditions, utilizing health care professionals and their surrounding Amish community members as resources. Amish families' management strategies lie across a spectrum from home-oriented to medical-oriented, and this spectrum is elaborated in the findings and discussion of this article.